A Practical System For Collecting And Characterizing Relatively Large Samples Of Airborne Dust From Mines - Erol Kaya; Jan M. Mutmansky; Richard Hogg (Society for Mining, Metallurgy & Exploration, 1993)
Characterization of the size, shape, chemical composition, and mineralogical content of mine airborne dusts generally requires a larger mass of dust particles than is typically collected using traditional sampling devices. In this paper, the general design of a passive dust collector is described and the field results are presented. The collector was constructed of galvanized sheet metal duct with a resin-coated honeycomb to provide an elutriation-type system for particle collection. Several versions of the collector were used in the field portions of the research. The dust samples collected from underground coal mines were found to possess angular particle shapes, relatively consistent size distributions, and elemental compositions that showed relatively little variation, at least for the more prevalent elements. In addition, the distributions of particles sizes obtained from the passive dust collector appear to be similar to those of samples collected at the same time in a conventional personal sampler except that the passive device seems to collect a larger quantity of coarse, non- respirable particles. Conclusions on the suitability of this dust collector for collecting characterization samples are presented. In addition, the potential for using such a dust collection system for supplying dusts for biomedical research is discussed.